Political Environment and the Use of Energy Resources in Nigeria - Agbanike, Tobechi F.; Chukwu, Anayochukwu Basil; Eteng, Mary J.; Ogwuru, Hycenth O.R.; Anochiwa, Lasbrey I.; Ogbuagu, Anuli R.; Nwaeze, Nnamdi C.; Okwor, Sunday A.; Anyanwu, Clara K. (International Journal of Energy Economics and Policy, 2022)
This study examines the dynamic relationship between political environment and the use of energy resources in Nigeria covering the period from 1978-2017 using the autoregressive distributed lag (ARDL) bounds testing approach. The results reveal that democracy has a significant long run and short run positive influence on energy consumption in Nigeria. However, the positive effect decreases significantly with an increase in the level of oil dependence in the short run. The results of this study in general support the view that high dependence of political democratic structures on oil wealth influences the positive effects of democracy in making public goods available in developing net oil-exporting economies. Economic diversification in Nigeria may therefore require formulating policies that will enhance access to clean energy sources in the economy.